Relationship between dominant decision-making style and creativity of nursing managers: A cross-sectional study - Eman Kamel Hossny; Hammad S. Alotaibi (BMC, 2024)
Abstract Objective This study aims to investigate the connection between dominant decision-making style and creativity among nursing managers. Background The dominant style of decision-making nursing managers use definitely affects the quality of decisions. Also, in another way, it can develop a skill of creative thinking that may influence the entire health care system. Methods Data from 229 nursing managers in four university hospitals were gathered using a cross-sectional study methodology and questionnaires about general decision-making styles and managerial creativity. Results nursing managers are highly creative. In general, the dominant decision-making style is rational and is correlated positively with creativity. Dependent style is the second one, while it is correlated negatively and significantly with creativity. Intuitive style is the third one and correlated negatively but is insignificant with creativity. Regression analysis revealed that only three styles have an effect on creativity: rational (positive), dependent (negative), and avoidant (negative), respectively. Conclusion The most dominant style is rational, which has the highest effect, which is positive on creativity. The dependent is the second dominant style and has a negative effect. Whereas intuitive is the third dominant style and did not have any effect on creativity.